Economics of sustained production of cardamom (Elettaria cardamomum M.) - KORIKANTHIMATH, V S (Journal of Spices and Aromatic Crops, 1995)
Large scale field trials were conducted by adopting High Production Technology at Chettalli (Coorg District, Karnataka, India) to study labour utilisation, input requirement and economics of cultivation of cardamom (Elettaria cardamomum). A highest yield of 1625 kg/ha (dry) was recorded during the fourth year after planting. The average of nine crop seasons - 695.66 kg/ha (dry) obtained in the trials was 12 times more than the national average yield of 58 kg/ha. Cultivation of cardamom was highly labour intensive. Out of 747.42 labour days required per haJyear during bearing period, the requirement of women labourers was higher (64.05 per cent); 63 per cent of the labour requirement was for harvesting and processing alone. The annual maintenance cost was Rs. 35,148.00/ha. Partitioning of various inputs indicated that maximum expenditure was incurred towards labour (including supervisory charges) i.e., Rs. 19,574.50/ha (55.69 per cent). A net income ofRs. 1,09,967.11/ha (average of nine crop seasons) was obtained with a production cost of Rs. 57.22/kg (dry).